Euro-Atlantic System and International Security in the Multi-Polar World (Economic and Political Thought, 2013)
The article is an attempt to answer a question what the role of the Euro--Atlantic system in the multi-polar world will be and if it will be able tosafeguard peace and security in the world. Will it be able to compete with thegrowing super-powers of China, India, Russia and other emerging powers?The author presents a thesis that it is very difficult to answer those questionstoday because the world is becoming less and less predictable and the dynamicof changes is unprecedented. Additionally, it remains in the shade of thestill existing financial and economic crisis and it is hard to say when it is goingto finish and what the consequences for the USA, the European Union andother participants of the international relations will be.The author demonstrates that a new, multi-polar and multi-civilizationworld order is being created today, and the period between 1991 and 2010proves that the Atlantic Community was not prepared for the collapse ofthe bipolar order and the Soviet Empire, which was believed to be the greatestthreat for the international peace and security. Moreover, the authorconsiders whether a renaissance of the Atlantic Community is possible andwhether it could play the same role in the 21st century as it used to play underthe leadership of the USA in the late 20th century. He suggests that if theAtlantic Community overcomes the present impasse, it will be a co-author ofa new international multi-polar order. However, if it does not, the world willface a chaos, conflicts and wars for years because China or India will not bestrong enough for several or even dozens of years to create a new peacefulinternational order without or with the marginalized Atlantic Community.